How to Build Healthy Societies: A Thematic Analysis of Relevant Conceptual Frameworks - Devaki Nambiar; Amy Bestman; Siddharth Srivastava; Robert Marten; Sonam Yangchen; Kent Buse (Kerman University of Medical Sciences, 2023)
Background  As the Sustainable Development Goals deadline of 2030 draws near, greater attention is being given to health beyond the health sector, in other words, to the creation of healthy societies. However, action and reform in this area has not kept pace, in part due to a focus on narrower interventions and the lack of upstream action on health inequity. With an aim to guide action and political engagement for reform, we conducted a thematic analysis of concepts seeking to arrive at healthy societies.Methods  This paper drew on a qualitative thematic analysis of a purposive sample of 68 documents including political declarations, reports, peer reviewed literature and guidance published since 1974. Three independent reviewers extracted data to identify, discuss and critique public policy levers and 'enablers' of healthy societies, the "how."Results  The first lever concerned regulatory and fiscal measures. The second was intersectoral action. The final lever a shift in the global consensus around what signifies societal transformation and outcomes. The three enablers covered political leadership and accountability, popular mobilization and the generation and use of knowledge.Conclusion  Documents focused largely on technical rather than political solutions. Even as the importance of political leadership was recognized, analysis of power was limited. Rights-based approaches were generally neglected as was assessing what worked or did not work to pull the levers or invest in the enablers. Frameworks typically failed to acknowledge or challenge prevailing ideologies, and did not seek to identify ways to hold or governments or corporations accountable for failures. Finally, ideas and approaches seem to recur again over the decades, without adding further nuance or analysis. This suggests a need for more upstream, critical and radical approaches to achieve healthy societies.